Mechanisms involved in p53 downregulation by leptin in trophoblastic cells. Issue 11 (November 2015) - Toro, Ayelén Rayen; Pérez-Pérez, Antonio; Corrales Gutiérrez, Isabel; Sánchez-Margalet, Víctor; Varone, Cecilia Laura
Abstract: Leptin, a 16-kDa polypeptide hormone, is produced by the adipocyte and can also be synthesized by placenta. We previously demonstrated that leptin promotes proliferation and survival in placenta, in part mediated by the p53 pathway. In this work, we investigated the mechanisms involved in leptin down-regulation of p53 level. The human first trimester cytotrophoblastic Swan-71 cell line and human placental explants at term were used. In order to study the late phase of apoptosis, triggered by serum deprivation, experiments of DNA fragmentation were carried out. Exogenous leptin added to human placental explants, showed a decrease on DNA ladder formation and MAPK pathway is involved in this leptin effect. We also found that under serum deprivation condition, leptin decreases p53 levels and the inhibitory leptin effect is lost when cells were pretreated with 50 μM PD98059 or 10 μM LY29004; or were transfected with dominant negative mutants of intermediates of these pathways, suggesting that MAPK and PI3K signaling pathways are necessaries for leptin action. Additionally, leptin diminished Ser-46 p53 phosphorylation and this effect in placental explants was mediated by the activation of MAPK and PI3K pathways. Finally, in order to assess leptin effect on p53 half-life experiments with cycloheximide were performed and MDM-2 expression was analyzed. Leptin diminished p53 half-life and up-regulated MDM-2 expression. In summary, we provided evidence suggesting that leptin anti-apoptotic effect is mediated by MAPK and PI3K pathways. Highlights: Study of leptin effect on placental survival. Leptin diminished p53 expression level signaling through the PI3K and MEK cascades. Leptin diminished p53 half-life and enhanced MDM-2 expression. Implication of leptin on apoptotic regulation during placentation.